Groundwater flow modeling for cachar, India using MODFLOW: a case study. Issue 2 (3rd April 2022) - Singh, Mrinal Kumar; Ghosh, Susmita
ABSTRACT: Cachar district of Assam, India has less cultivated land due to waterlogging of agricultural land in the monsoon period and shortage of surface water in the dry season. But, the area has untapped enormous groundwater which can be extracted from the aquifer to increase cultivation in the dry season. In this regard, a detailed analysis of the groundwater system and a feasible plan for sustainable groundwater management are required. Therefore, a transient state groundwater flow model was developed for the region using MODFLOW. The model was calibrated and validated using the observed groundwater level (1996–2015). The groundwater recharge was estimated using GEC 1997. The results from the model study indicated that the total inflow to the aquifer is 28.47 million cubic meters (mcm) and the outflow is 27.45 mcm. Hence, the rising trend of water level and more waterlogged area were observed. A high hydraulic gradient was visualized in the area vicinity to river Barak, where the flow direction is towards the aquifer in monsoon, and vice-versa in the nonmonsoon period. The model was further predicted for a hypothetical scenario by proposing additional pumping wells for groundwater utilization in agriculture and to reduce the waterlogged areas. Sensitivity analysis shows that model is more sensitive in recharge than hydraulic conductivity.